PENGARUH PENGUATAN OTOT RECTUS ABDOMINIS TERHADAP PENURUNAN TFU PADA IBU POSTPARTUM PERVAGINAM DI BPM KABUPATEN SLEMAN - fitriahadi, enny (Jurnal Kebidanan, 2019)
Complications that occur during childbirth usually experience bleeding, sub involusio uteri, swollen breast, nipple blisters etc. By handling and supervising the correct and precise complications during the puerperium will decrease so that morbidity and mortality in the mother will decrease. This study aims to determine the effect of rectus abdominis muscle strengthening on the decrease in uterine fundus height in vaginal postpartum mothers in BPM Sleman District. The purpose of this research is to know the decrease of fundus uteri level (TFU) before and after intervention of rectus abdominis muscle strengthening. The sample in this study amounted to 15 respondents and 15 respondents with the control group. This research method uses quasi experimental with non-randomized pretest-posttes group design. The sampling technique uses total sampling. Different test results of pre test and post test in experimental or non experimental group using Wilcoxon and Mann Whitney. The result of this research shows that the majority of TFU decrease in intervention group is fast 10 (66.6%) while in the control group decrease TFU is slow 9 (60%), and based on bivariate analysis results obtained p-value 0,003 which means there is influence of rectus abdominis to decreased TFU of postpartum mother. The main suggestion for postpartum mothers is expected to be able to perform early and regular early mobilization, especially the strengthening of abdominal rectus abdominal muscles that can decrease TFU so that the period of uterine involution can run faster.